Dampak Eksistensi Alfamidi Dan Indomaret Terhadap Ritel Tradisional Di Kecamatan Parigi - Atista Galuh Surya Putri; Eko Jokolelono; Laendatu Paembonan; Rita Yunus; Santi Yunus (Penerbit Goodwood, 2025)
Purpose: This study aims to understand the impact of modern retail, particularly Alfamidi and Indomaret, on income levels and the sustainability of traditional retail businesses in Parigi District, Parigi Moutong Regency. It focuses on how traditional retailers are affected and how they respond to competition. Methodology/approach: This research uses a descriptive qualitative approach and is conducted in the Parigi District. Data were collected through purposive sampling using observations, in-depth interviews with traditional business owners, and documentation. The data were analyzed using thematic techniques, such as data reduction, presentation, and conclusion drawing. Results/findings: The findings reveal that the emergence of modern minimarkets has intensified competition, resulting in a decline in customers and income for traditional retailers. Consumer shopping preferences have shifted due to competitive prices, wider product selection, and better facilities offered by minimarkets. Nevertheless, some traditional retailers have started to adapt by innovating their product offerings and improving their service qualit. Conclusion: The presence of minimarkets in the Parigi District presents both challenges and opportunities. While many traditional businesses experience reduced income, others attempt to survive by adjusting to market demands through innovation and differentiation. Limitations: This study did not include quantitative measurements of income decline or behavior change, limiting the precision of its economic impact analysis. Contribution: This research provides important insights for local policymakers to design fair competition strategies and support traditional micro and small businesses to ensure a balanced and sustainable retail ecosyste.